Ictiofauna associada aos espigões de uma praia arenosa no Nordeste do Brasil: Estrutura da assembleia, Ecologia trófica e Impactos antropogênicos - Dantas, Natália Carla Fernandes de Medeiros (2019)
Sandy beaches are subject to a number of threats and anthropogenic changes such as recreational activities, pollution (debris, domestic sewage, industrial effluents and oil spills), exploitation and extraction of resources such as fishing, development and construction of coastal defense engineering structures (breakwater). However, such actions alter the landscape, the quality and health of these ecosystems in a significant way. The objective of this research is to describe the structure of the fish assemblage associated with two breakwater and to analyze the influence of environmental factors in this structuring, as well as to describe and analyze the trophic ecology and to identify, classify and quantify the microplastic ingested by seven species of fish in one sandy beach of Northeast Brazil. The study was carried out in the coastal zone of Fortaleza - CE, in the urban beach of Meireles. The collections occurred monthly, in the low tide of sygyzy, from November of 2015 to January of 2017 along two breakwater distant 1.4 km each other. Samples were collected in the windward and leeward sides of each breakwater. The fish were caught using a trawling net (15 m long, 2 m high, 2 m deep bag and 3 cm mesh). Were captured a total of 3045 individuals belonging to 26 families and 74 species. The fish assemblage was structured differently between the windward and leeward sides, however the more pronounced differences occur between the two breakwater than between the sides of the same breakwater. Hydrodynamics may have generated the changes observed in the assembly. Precipitation did not generate an increase in abundance in any of the studied sites, indicating that local factors and interferences overlap with regional factors (precipitation). Increased pollution (quantity of debris) has led to a decrease in the number of species and diversity in one of the breakwater. High frequency and abundance of microplastic ingestion were observed in the seven species studied (Opisthonema oglinum, Catreops spixii, Sciades herzbergii, Chloroscombrus chrysurus, Conodon nobilis, Haemulopsis corvinaeformis). The abundance of ingestion and the type of microplastic ingested does not depend on the feed habit of the species or its length, since larger individuals did not consume a greater abundance of microplastic. The most commonly ingested type of microplast was the blue fibers. Studies that broaden the scientific understanding of how sandy beaches respond ecologically to the threats and anthropogenic impacts on which they are subject are crucial to predict the consequences of these impacts, especially as sandy beaches are such a widely threatened environment around the world.